Quantifying Treatment - Outcome in Maxillo-Facial Injuries - Agarwal, Anil; Chari, P S; Mitra, S (Indian Journal of Plastic Surgery, 1994)
Statements regarding outcome in Plastic Surgery are often subjective and lack reproducibility, mainly because of lack of quantification of aesthetic issues. A method is being presented using maxillo-facial injuries as a prototype, to resolve virtually any plastic surgical problem into 3 basic components – Function, Aesthetics and Psycho-social. Unfavourable results are graded according to a strictly defined protocol. Aesthetic evaluation is performed by the patient and relatives/friends in a manner designed to reduce subjectivity and physician-induced bias.The system provides a comprehensive patient-satisfaction index which has been found useful for everyday post-surgical assessment and computer-based data-recording. It allows us to quantify results, pin point shortcomings and foster a desirable doctor-patient relationship.With the use of such a system it should be possible to document, compare and even predict treatment-outcomes with a degree of precision not previously achieved.